Proposta de método para avaliação do processo de extração de sucos cítricos - Kharfan, Daniela (Universidade Federal de São Carlos, 2011)
For almost one century, citrus chain has been one of the most important agribusiness for Brazil. Brazil is the largest world orange producer and the largest orange juice exporter, responsible for almost 90% of the worldwide orange juice exportations. Doubtless one of the most important Brazilian sectors, citrus is responsible for a huge percentage of the agribusiness exportations (around USD 1,5bilion/year) and one of the economy motors of the central regions of the State of São Paulo. Over this period, many changes occurred and are still going on into the national and international scenarios. Also, in the XXI century changes have being happened more quick and intense: great fruit and orange juice price oscillations, influence of exchange variation, the 2008 economical crisis, influence of climate conditions and incidence of new diseases, besides demand variations regarding volume and type of product (advent of NFC Not From Concentrate or single strength juice). Citrus processing industry represents a fundamental key role in the whole chain, to achieve new frontiers, putting the Brazilian product into the 5 continents, leveraging exportations to almost 1,300 k/tons of juice exported annually. To guarantee competitiveness in the business, processors have searched continuous improvement on processes, equipment, management techniques as well as quality standards of their products, in order to meet the demands of the market that, year by year, have become more discerning and demanding. There is also the need of continuous improvement and adjustment of the Research & Development techniques for equipment applied to industry, to attend the new parameters. Performance tests of citrus juice equipment are totally important to: evaluate productive process efficiency, investment definition, meet customer s standards and represent a point that impacts the strategic corporate decisions. The purpose of this master s degree dissertation is to propose a method for evaluating the technical-economic stage of citrus juice extraction. The study aims the juice extraction process introduced in the citrus juice extraction chain. For this, it was performed a review of literature and a case study in the segment of citrus juice processing. The research approach used is qualitative and quantitative, using already existent data, from empirical studies conducted in the sector. This work aims to structure and propose a method for the process of citrus juice comparative tests, and the performance evaluation of the extraction system, considering the higher number of variables and ensuring all necessary and sufficient data for decisionmaking. As academic contribution, this work aims to bring an empirical example improvement of food industry equipment, using experimental techniques and data analysis in a specific juice extraction situation, whose results are used for tracking their productive processes, monitoring and improving performance and decision-making regarding changes and investments.
Keywords: Engenharia de produção; Citricultura brasileira; Indústria; Desempenho técnico; Método; Citrus; Citrus juice extraction; Method to evaluate operation; Techno-economic performance; ENGENHARIAS::ENGENHARIA DE PRODUCAO